Job Autonomy sebagai Moderator pada Pengaruh Job Insecurity terhadap Perilaku Kerja Inovatif - Ardy, Ludi Prasetyo; Fajrianthi, Fajrianthi (Jurnal Psikologi Teori dan Terapan, 2019)
This study aims to examine the role of job insecurity towards innovative work behavior with job autonomy as a moderator. The concept of the three variables were tested using the theoretical concepts of job demand and job control. In the condition of "active job", individuals can produce ideas and innovations in responding to work conditions. Previous studies show that active jobs can be obtained when there is a high interaction between high job demand and job control. Based on these studies it can be assumed that job insecurity (job demand) and job autonomy (job control) will influence innovative work behavior. This study used a quantitative approach by using SEM-PLS to analyze data. A total of 194 participants in a manufacturing industry, primarily from its production units, were involved in this study. The results show that job insecurity has a negative significant effect on innovative work behavior while job autonomy has a positive significant effect on the variable. The moderation test of job autonomy on the effect of job insecurity on innovative work behavior show no significant result. The strict operational standard procedure in the production unit is assumed as one of the factors that makes job autonomy does not play a role in reducing the negative influence of job insecurity on innovative work behavior.Keywords: Job autonomy, job insecurity, innovative work behavior, manufacturing